Reverse-topology membrane scission by the ESCRT complexes - Schöneberg, Johannes (Nat Rev Mol Cell Biol, 2016)
The narrow membrane necks formed during viral, exosomal, and intra-endosomal budding from membranes, cytokinesis, and related processes have interiors that are contiguous with the cytosol. The severing of these necks involves action from the opposite face of the membrane as compared to the well-characterized coated vesicle pathways, and is referred to as “reverse” or “inverse” topology membrane scission. This process is carried out by the endosomal sorting complexes required for transport (ESCRT) proteins. In particular, the ESCRT-III proteins can form filaments, flat spirals, tubes and conical funnels, which are thought to somehow direct membrane remodeling and scission. Their assembly, and their disassembly by the ATPase VPS4, has been intensively studied, but the mechanism of scission has been elusive. New insights from cryo-electron microscopy and various types of spectroscopy may finally be close to rectifying this situation.